Causal relationship between Baff-R expression and normal pressure hydrocephalus: insights from Mendelian randomization analysis - Wencai Wang; Luyao Ma; Menghao Liu; Yongqiang Zhao; Wei Ye; Xianfeng Li (BMC Neurology)
Abstract Objectives Previous studies have suggested a possible link between normal pressure hydrocephalus (NPH) and immune factors, but the causal relationship between NPH and Baff-R expression on immune cells remains enigmatic. This study used a Mendelian randomization (MR) method to elucidate this association. Methods The study used data from the Finngen genome-wide association study (GWAS) and included a large European cohort of 767 patients with NPH and 375,610 controls. Baff-R genetic results in 3,757 individuals of European ancestry had 22 Baff-R-related traits. Different MR techniques were used, and efficacy was assessed using heterogeneity and sensitivity analyses. Results and conclusion Among the 22 traits, 8 Baff-R-related traits were causally related to NPH. The genetic prediction indicates that Baff-R, particularly in the area of BAFF − R on unswitched memory B cell, BAFF − R on IgD + CD38 − B cell, BAFF − R on CD24 + CD27 + B cell, BAFF − R on IgD − CD38 − B cell, BAFF − R on IgD + CD38dim B cell, BAFF − R on IgD + CD24 + B cell, BAFF − R on IgD + CD38 − naive B cell, BAFF − R on memory B cell may decrease risks on the development of NPH. These findings may help us to understand the immune mechanisms associated with NPH and help to develop future biomarkers related to the disease.